Two-Layer Storage Scheme and Repair Method of Failure Data in Wireless Sensor Networks. (8th October 2012) - Shen, Yulong; Dang, Xiaowei; Shu, Min; Xi, Ning; Ma, Jianfeng
Abstract : Distributed data storage is a key technology in the data collection in wireless sensor networks. The storage scheme based on network coding is applied to data collection in wireless sensor networks because of its high reliability and low overhead. However, it is an open problem to reduce data repair communication overhead caused by the failure of storage nodes. This paper focuses on this issue and presents a two-layer distributed data storage scheme. The lower-layer nodes store the encoded data blocks and the upper-layer nodes store the re-encoded blocks that are responsible for failure data recovery. Based on the two-layer data storage scheme, a data repair method is proposed to decrease the repair communication overhead with only sacrificing lower storage overhead. Compared with MSR, interference alignment-based scheme and group interference alignment scheme, the proposed method has lower repair communication overhead. We prove that the proposed method can reduce the repair communication overhead to o ( 1 / k ) times and it is suitable to resource-constrained distributed wireless sensor networks.